The role of focal adhesion kinase in bladder cancer - Markovič, Gaja (Radiology and oncology (Ljubljana), 2025)
Background: Focal adhesion kinase (FAK), a cytoplasmic tyrosine kinase, plays a crucial role in focal adhesion turnover by interfacing between the extracellular space, transmembrane integrins, and actin filaments. Its significance for the progression of several malignancies, including bladder cancer, has been well-documented. However, its precise role and the implications of its inhibition in bladder cancer tissues and urothelial in vitro models has not been fully explored. This study examined FAK expression and function in human bladder cancer biopsies and in vitro bladder cancer models. Materials and methods: Ex vivo analyses were performed using reverse transcription-quantitative PCR (qRT-PCR), western blotting, and immunohistochemistry to compare FAK expression between bladder cancer tissues and adjacent normal tissues. In vitro, FAK expression was assessed in low-grade (LG) human non-invasive papilloma urothelial cell line RT4 for NMIBC (Ta), high-grade (HG) human muscle-invasive cancer urothelial cell line T24 for MIBC (T2) and normal porcine urothelial (NPU) cells using qRT-PCR and western blotting, as well as flow cytometry for the quantification of FAK-positive RT4 and T24 cells. The role of FAK in cancer cell survival was explored in vitro using microRNA (miRNA) to silence FAK expression. Additionally, we used FAK inhibitors PND-1186, PF-573228 and defactinib to investigate the effects of FAK inhibition on normal compared to cancerous bladder urothelial cells. Results: Ex vivo analyses demonstrated significantly higher FAK expression in bladder cancer tissues compared to adjacent normal tissues. Similarly, in vitro analyses showed significantly higher FAK expression in RT4 and T24 cells than NPU cells. Silencing FAK using anti-FAK plasmids led to increased caspase-3-mediated apoptosis of RT4 and T24 cells and growth reduction of stably transfected T24 cells. Importantly, based on cell viability assays, treatment with 100 µM defactinib for 2 hours per day on 3 consecutive days was identified as a clinically relevant regimen. Under this treatment, the viability of differentiated NPU cells remained high at 108.4 ± 17.1%, while the viability of 2-day RT4 and 2-day T24 cells was drastically reduced to 4.1 ± 2.7% and 7.6 ± 2.9%, respectively. Conclusions: To our knowledge, this is the first report demonstrating the role of FAK and its inhibition across both normal and cancerous bladder urothelial models. This study highlights the critical role of FAK in the progression of human bladder cancer and establishes a foundation for exploring FAK inhibition as a potential therapeutic approach in bladder cancer treatment.
Keywords: bladder cancer; defactinib; defaktinib; focal adhesion kinase; fokalna dhezijska kinaza; human urothelial carcinoma; humani urotelialni karcinom; rak mehurja; urotelijska celica; urothelial cell